Biuletyn Informacyjny . no. 5, 1980 - Komitet Założycielski Niezależnego Samorządnego Związku Zawodowego "Solidarność" przy Stoczni im. Komuny Paryskiej Gdyni (KZ NSZZ Stocznia Gdyńska, 1980)
Creation and circulation: In early 1989 interrim Solidarity organization in the Komuna Paryska Shipyard published a number of issues of the still illegal publication